Gramática normativa: movimentos e funcionamentos do “diferente” no “mesmo” - Surdi, Marcia Ione (2010)
This study aims to investigate and comprehend the movements and functionings that make emerge the heterogeneity in the discourse that preface the grammar, that is, how the different is presented in the same , in the normative grammar. The object that was selected to be analyzed is made up of four editions of the Normative Grammar of Portuguese Language (NGPL), by Carlos Henrique da Rocha Lima, as corpus. The proposal is developed according to the theoretical - methodological perspective of Discourse Analysis, placed in relation with some proper notions to the carried out studies under the aegis of the History of Linguistic Ideas. The study is sub-divided into three parts, named and constituted as: In Part I, The different in the same : the object of look under a discursive point of view , the theme and the theoretical research conducted are presented, electing the concepts and the references that support the analytical device. In Part II, And the Normative Grammar is arising... , the ircumstantialization process of the analysis object is set out, considering so the historical-discursive elements, as an attempt to bring out the theoretical over turns of the NGPL production and the conditions of production in which the grammatical subject is inserted. In Part III, Returning from Rocha Lima to Normative Grammar , we developed our gesture of interpretation into two movements of analysis. We started by the covers reading of our object of study, observing the differences and similarities among the imagetic compositions and how they transform themselves into the time line, in a regressive way, returning to its appearance. In the second movement, we saved space to what preface the NGPL in verb and no longer in image, observing and analyzing how the different moves itself and functions in the same . In a succinct way, we can say that in relation to the analyzed discursivities, we observed the functioning of the different in the same in several moments: in the covers we have the verbal regularization as well as the graphic-imagetic renewal which show the functioning of the different directions, affected by the production conditions of the doing grammatical normative in Brazil; in the texts that compose the prefacing of NGPL, we identified marks of resistance and memory as well. The different shows itself by the resistance marked by the position of the grammatical subject in relation to the Brazilian Grammatical Nomenclature (BGN); and by the entrance of the Linguistic science knowledge. The same shows itself by the maintenance, by the grammatical regularity of the discourse where the memory of knowledge about the language emerges. The analyze of these discursive materialities shows us that the imaginary project of the normative grammar also constitute itself by the failures in the language, as the heterogeneous appears, slips and functions, therefore moves in the same , since the different is constitutive of the language grammar.